42. IDEA BANGSA TERBAIK MENURUT PERSPEKTIF SEJARAH DAN PERADABAN: EXPLORING NOTIONS OF THE "BEST NATION" THROUGHOUT HISTORY AND CIVILIZATION - Khalid, Nurul Khairiah; Abdul Basir, Mukhamad Khafiz; Ali Hasan, Ahmad Rozaini; Wan Jamil, Wan Jamil (Journal of Islamic, Social, Economics and Development, 2024)
Menstrual education holds significant importance within the realm of health education in primary schools in Malaysia. However, the current menstruation education curriculum in primary schools in Malaysia significantly lacks attention to addressing the unique requirements of Muslim females, who constitute the majority of the population in the nation. This study aims to review the prospects and challenges of the model of Islamic menstrual education in Malaysian primary schools. This study has identified several prospects for implementing Islamic menstrual education in Malaysian primary schools, including: (a) improving understanding of Islamic guidelines related to menstruation; (b) empowering adolescent Muslim females to practice their faith; (c) increasing awareness and reducing doubts among parents and teachers; and (d) fostering cultural sensitivity among society in the targeted population. A few challenges were highlighted in this study regarding the implementation of Islamic education, namely: (a) misconceptions and myths related to menstruation in Islam; (b) limited trained personnel for educating; (c) resistance to change in societal mindset; and (d) lack of resources in governing. In conclusion, this study uncovers noteworthy opportunities and obstacles to the improvement of comprehensive menstruation education among adolescent Muslim females. Future studies should explore various avenues to improve current procedures and outcomes, as indicated by this study.